The fundamentals of telemetry pipelines and how they are used to maintain application performance - Miles, Russ; Alvason, Kai (O'Reilly Media, Inc., 2024)
If you're a DevOps engineer, SRE, or security engineer struggling under a deluge of telemetry data, this report is for you. High-quality metrics, traces, and logs are all essential for observing and working with modern systems, but when they're applied to a complex cloud-based system the result can be a confusing mess. This insightful report explains the promise of telemetry pipelines and shows you how to use pipeline tools to master the flood of telemetry data. Author Russ Miles dives into key concepts, provides real-world examples, and shows you how to build your own telemetry pipelines. By the end of this report, you'll understand how investing in telemetry pipelines lets you apply valuable business cases such as compliance and cost management.
Includes bibliographical references
Keywords: Application program interfaces (Computer software); Cloud computing; Interfaces de programmation d'applications; APIs (interfaces)